The contemporary state of intellectual forming skills of future informatics teachers - Morkvian, I. V. (Problems of Engineer-Pedagogical Education, 2018)
The necessity of intellectual skills formation of the future informatics teachers for continuous self-development and self-improvement in professional activities are mentioned in the article. In the course of the study the essence of understanding the concepts of "intellectual ability", "intelligent informatics teacher’s skills ", "intellectual skills formation science teachers" are put forward. It is said the important role of natural and mathematical sciences in the professional training of future science teachers which helps to create the classroom conditions for effective intellectual work of the students' intellectual skills which needed for the creation of educational software in the study of these subjects. Among the components of the individual are selected intellectual skills such as motivation, Gnosticactivity and competence, personal and presents their content and structural elements. The basis for the development of diagnostic tools for the study of the levels of intellectual skills of future Informatics teachers is defined criteria such as motivation, contents and evaluative-effective and appropriates these indicators. Indicated that criteria and indicators are considered as signs of formation of intellectual skills of the future teachers of computer science that are used to determine their readiness for the creative professional activities. Thus, the formation of indicators of future science teachers to the profession allocated to low, medium, and high enough level, given their description and characteristics of students who meet certain levels. Indicated research findings and the reasons for this situation are noted and future areas of research are reduced.